Predictive Factors for Vitamin D Concentrations in Swiss Athletes: A Cross-sectional Study - Zürcher, Simeon Joel; Quadri, Andrea; Huber, Andreas; Thomas, Lothar; Close, Graeme Leonard; Brunner, Saskia; Noack, Patrik; Gojanovic, Boris; Kriemler, Susi (Sports Medicine International Open, 2018)
Vitamin D concentrations corresponding to 75 nmol/L 25(OH)D have been associated with maintained muscle function, growth and regeneration, optimal bone health and immunology in athletes. The objective of this study was to investigate the prevalence and predictors of insufficient 25(OH)D concentrations in athletes. Six hundred three Swiss athletes were assessed. 25(OH)D was analysed by high-performance liquid chromatography (HPLC). A standardized questionnaire was used to gather information about potential predictors for 25(OH)D concentrations; 50.5% showed insufficient 25(OH)D concentrations. Differences in predicted probability of insufficient 25(OH)D were found for those vitamin D supplemented (42%) versus not supplemented (52%), in those performing indoor (58%) versus outdoor sports (43%), and during the sun-deprived seasons of fall (49%), winter (70%) and spring (57%) compared with summer (17%). Higher BMI z-scores and age were associated with higher 25(OH)D concentrations. In conclusion, insufficient 25(OH)D concentrations were common among athletes especially at a younger age, among those not supplemented, in athletes who trained indoors, and during the sun-deprived seasons. Because the prevalence of insufficient 25(OH)D concentrations in this study was high, regular supplementation in athletes may be indicated, except perhaps during the summer season. Further research is needed to determine which 25(OH)D concentrations lead to optimal health and performance in athletes.
Keywords: 25(OH)D; 25-Hydroxyvitamin D; Pre-participation examination; Supplementation; Season; Youth